Вычислительный метод определения постоянных проективного преобразования координат системы координат текущего кадра в систему координат базового - Белоус, Н. В.; Красов, А. И. (НТУ "ХПИ", 2017)
В статье разработан вычислительный метод определения постоянных проективного преобразования системы координат текущего кадра в систему координат базового. Выбор наилучшего проективного преобразования позволяет найти наилучшие параметры сложения кадров. Особенно в темное время суток это является единственным способом подготовить изображение номерного знака к его различению автоматически или с помощью эксперта. Вычислительный метод обеспечивает трансформацию изображения номерного знака текущего кадра в изображение номерного знака базового кадра, свободную от различного вида искажений. В статье для оценки параметров прямой по изображению ее отрезка на цифровом изображении использован метод моментов, как простой, надежный и часто используемый на практике. Предложенный метод обеспечивает надежное начальное приближение нелинейного преобразования и поиск соответствующих ему постоянных. Переход к нелинейным трансформациям необходим, например, при изогнутости номерных знаков или других носителей текстовых данных.

Computational method for determining projective transformation constants of the current frame into basic coordinate system is developed. Choosing the best projective transformation allows finding the best settings for adding frames. It is the only way to prepare the license plate image to automatic distinction or distinction with the help of an expert at night. This computational method enables the transformation of the current frame license plate image into the image of the base frame license plate that is free of various types of distortions. The article provides direct assessment of the section parameters of digital image using the method of moments, as a simple, reliable and commonly used in practice. To set the projective mapping inverse mapping is used so that each reference point of the license plate on resulting photos is associated with coordinates on the license plate plane. The corners of the license plate are used as reference points. The considered metod allows adding images of license plates. The proposed method provides for reliable initial approximation of a nonlinear transformation and searching constants corresponding to it. The transition to non-linear transformation is required, e.g. when there are curvatures of license plates or other text data carriers.
Сomputational method for determining projective transformation constants of the current frame coordinates into basic coordinate system
Keywords: реперные точки; трансформация изображения; цифровое изображение; вычислительный метод; projective transformation; reference points; digital image